Understanding climate change adaptation: the role of citizens’ perceptions and appraisals about extreme weather events - Domingos, Samuel (2019)
Climate change is driving dramatic environmental changes and posing new demands to citizens, health authorities, and policy makers worldwide. This is due to an increased frequency, intensity, and duration of associated extreme weather events. Recent calls for better understanding of how citizens adapt to such demands and the role that psychological processes’ play in that adaptation, have been put forward. We contributed in this regard by (1) applying the Biopsychosocial Model of Challenge and Threat (e.g. Blascovich 2008) to the study of human responses (psychological, physiological, and behavioural) to extreme weather events; (2) using it as the conceptual basis for a mixed methods study aimed at exploring citizens’ perceptions, beliefs, and appraisals of the demands posed by such events and available resources to cope with them. Preliminary qualitative results are presented and potential implications for stakeholders and policy makers in the climate change domain are discussed. An example of how such conceptual and methodological approaches may contribute to developing evidence-based strategies for incrementing citizens’ resilience and adaptation to climate change, will be provided. This allow a better understanding of citizen appraisals and perceptions’ role in shaping adaptive behaviour, in order to provide them with the necessary personal and social resources to cope with extreme weather events and increment future resilience.